"Sulle tracce del crimine. Viaggio nel giallo e nero Rai / Hot on the Heels of Crime. A Journey into the World of Detectives on Rai" (Cinéma & Cie. Film and Media Studies Journal, 2021)
"Sulle tracce del crimine. Viaggio nel giallo e nero Rai / Hot on the Heels of Crime. A Journey into the World of Detectives on Rai"(Roma, Museo di Roma in Trastevere October 7, 2020 – March 31, 2021)Exhibition and Catalogue Roma: RaiLibri, 2020